Acute type A aortic dissection in‐hours versus out‐of‐hours: A systematic review and meta‐analysis. Issue 12 (1st October 2020) - Toh, Steven; Yew, Dominic Choon Men; Choong, Jia Jin; Chong, Tze Lin; Harky, Amer
Abstract: Objective: We sought to compare clinical outcomes in patients with acute type A aortic dissection that undergone surgical repair during in‐hours (IH) versus out‐of‐hours (OOH). Methods: An electronic literature search was done till March 2020 to include studies with comparative cohorts of IH versus OOH. Primary outcomes were 30‐day mortality, stroke, and reoperation for bleeding; secondary outcomes were acute kidney injury, total hospital stay, and intensive care unit stay. Results: Six articles with a total of 3744 patients met the inclusion criteria. Mean age was similar, 60 ± 12 versus 60 ± 13 in IH versus OOH ( p = .25). Aortic root and total arch replacement were similar in both cohorts, 22% in IH versus 25% in OOH (risk ratio [RR], 1.10; 95% confidence interval [CI: 0.78, 1.55]; p = .58) and 29% in IH versus 32% in OOH (RR, 0.96; 95% CI [0.89, 1.04], p = .37) respectively. Reoperation for bleeding and stroke rate were similar, with 18% in IH versus 23% in OOH (RR, 0.89; 95% CI [0.73, 1.08]; p = .24), and 12% in IH versus 13% in OOH (RR, 0.83; 95% CI [0.66, 1.03]; p = .09) respectively. Thirty‐day mortality was significantly lower in IH (RR, 0.81; 95% CI [0.72, 0.90]; p = .0001). Conclusion: There was higher 30‐day mortality rate during OOH surgery, yet this difference diminished following sensitivity analysis. There were no significant differences in major postoperative outcomes. Therefore, operating on such cases should be decided on clinical priority without delay.